Conception, implantation et utilisation d’un portfolio professionnel étudiant dans un programme de formation en ergothérapie - Michèle Hébert; Jean-Pascal Beaudoin; Rachel Thibaut; Rita Pitre (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper presents the results of a Participatory Action Research on the design, implementation and ongoing use of a student professional portfolio at the University of Ottawa’s Occupational Therapy Program. The goal was to create an adult education tool that would allow students to develop and integrate all components of learning and professional growth.  Feedback from the research team and 70 students with a one-year experience in using the portfolio indicates that the tool is relevant and useful, but special attention must be given to developing a greater sense of ownership on the students’ part. Avenues for reflection are offered.